Measuring market concentration in the Aegean ferry system - Alexander M. Goulielmos; Giannis Sitzimis (SPOUDAI - Journal of Economics and Business, 2012)
The paper calculates the concentration in 6 major routes of the Greek ferry system (2001-2010), important not only for international tourism, including Cruises, but also for the cohesion of the Greek space with EU. Worth noting is the consolidation of companies that took place, where from 25 companies operated (prior of 1994) to 5 groups (by 2012). This was due to: (1) the abolition of cabotage (i.e. the right to restrict coastal services to national-flagged ships) by EU. The relevant legislation passed in 1992 with a long transition period (1992-2004), and (2) the listing of ferry companies in Athens Stock Exchange. Frequent buy-outs increased the monopoly power of companies involved. The Greek ferry system was a par excellence state-regulated one since 1976, with State issuing licenses and determining fares, but failing to control quality. A measure of monopoly power was calculated, based on the work of Lerner, Herfindahl and Hirschman, known as the Hirschman-Herfindahl. After a brief examination of what is meant by 'market', we provided the values of HHI for the 6 routes: (1) Piraeus-Crete, (2) Piraeus-Chios-Mytilene, (3) Crete (Iraklion)-Piraeus, (4) Piraeus-Crete (Rethymno), (5) Piraeus-Dodecanese and (6) Piraeus-Cyclades. These show a distinct pattern of oligopoly/monopoly, with the traffic concentrated in a small group of companies. We argue that the number of ships of different companies in one route determines the market. Neither partial (2002) or full (2006) deregulation had any effect in increasing competition, as expected, with the temporal exception in one or two cases. Moreover, Greek authorities had not prepared properly for deregulation and as a result failed either to prevent monopolies or to create the effective antitrust regulation like in USA.
Keywords: K23; L11; L12; L13; L22; L43; 330; Concentration; Greek ferry system; the Hirschman-Herfindahl Index; deregulation